Raba jezikovnih virov med učitelji na dvojezičnih šolah v Prekmurju - Kosem, Iztok (Slovenščina 2.0, 2017)
The paper presents the results of a survey on the use of different language resources (dictionaries, orthographies, thesauri, etc.) by teachers at bilingual schools in Prekmurje. The survey was conducted as part of the project focussed on developing a concept of a new comprehensive Slovenian-Hungarian dictionary. The dictionary aims to meet the needs of a wider community, as well as needs specific to bilingual education. The main aim of the survey was thus to establish how well teachers know language resources available to them, how often they use them during their work, and which types of dictionary information do they find useful. Furthermore, the survey also tried to find out which communication activities in the Hungarian language pose most problems to teachers. The analysis of the survey has shown that majority of teachers know available language resources, and also used them at their work. Due to various problems with communication in Hungarian, teachers need to use a wide variety of language resources, both bilingual and monolingual. The fact that many of the existing resources, especially bilingual ones, are not available in digital form, is definitely a major obstacle. Teachers consider all types of dictionary information to be important/useful, but especially translation equivalents, indication of the correct spelling, explanations of word meanings, and dictionary examples. Importantly, the types of information not available in existing resources, such as audio pronunciation and whole-sentence examples, are considered to be very useful. The survey findings will be considered in the preparation of a new comprehensive Slovenian-Hungarian dictionary, from headword selection to selecting the parts of dictionary microstructure. However, even more important is the fact that the findings have made us consider a more substantial inclusion of contents relevant for language production, gradual publication of the dictionary, prioritizing the compilation of certain types of entries, and compiling (and publishing) entries in layers. Such considerations mean bringing new approaches to Slovenian bilingual lexicography, dictated by lexicographic trends and enabled by state-ofthe-art lexicographic methods.
Keywords: dvojezično šolstvo; Prekmurje (Slovenija); narodne manjšine; vzgoja in izobraževanje; dvojezični slovarji